Stygobromus bakeri, a new species of groundwater amphipod (Amphipoda, Crangonyctidae) associated with the Trinity and Edwards aquifers of central Texas, USA - Randy Gibson; Benjamin T. Hutchins; Jean K. Krejca; Peter H. Diaz; Peter S. Sprouse (Subterranean Biology, 2021)
A new stygobitic groundwater amphipod species, Stygobromus bakeri sp. nov., is described from 4 central Texas limestone karst springs; John Knox Spring (Comal County), Jacob’s Well (Hays County), Mormon Spring (Travis County) and Salado Springs (Bell County). This species belongs to the predominately western Nearctic hubbsi species group of Stygobromus and differs from other species in the group by gnathopod 1 with row of 4 to 5 setae posterior to the defining angle, pereopods 6 and 7 with broadly expanded bases and distinct distoposterior lobes, gnathopods 1 and 2 with 2 rows of 3 singly inserted setae on the inner palm, and uropod 3 with single, slightly distal peduncular seta. Habitat, sympatric groundwater species, and conservation issues are discussed.